A study of latent profile analysis of empathic competence and factors influencing it in nursing interns: a multicenter cross-sectional study - Wang, Jia; Xu, Xiaoqing; Sun, Jiaxin; Ma, Yujia; Tang, Peijuan; Chang, Wenzhong; Chen, Xia; Cui, Yajuan; Su, Mei; He, Yan (Frontiers in Public Health, 2024)
Background Empathy, as one of the fundamental principles of nursing professionalism, plays a pivotal role in the formation and advancement of the nursing team. Nursing interns, as a reserve force within the nursing team, are of significant importance in terms of their ability to empathize. This quality is not only directly related to the degree of harmony in the nurse–patient relationship and the enhancement of patient satisfaction, but also plays a pivotal role in the promotion of the quality of nursing services to a new level. Aim The objective of this study was to gain a deeper understanding of the current state of nursing interns’ empathic abilities. To this end, we sought to examine empathic performance under different profile models and to identify the key factors influencing these profile models. Methods The study utilized 444 nursing interns from 11 tertiary general hospitals in Inner Mongolia as research subjects. The study employed a number of research tools, including demographic characteristics, the Jefferson Scale of Empathy, and the Professional Quality of Life Scale. A latent profile model of nursing interns’ empathy ability was analyzed using Mplus 8.3. The test of variability of intergroup variables was performed using the chi-square test. Finally, the influencing factors of each profile model were analyzed by unordered multi-categorical logistic regression analysis. Results The overall level of empathy among nursing interns was found to be low, with 45% belonging to the humanistic care group, 43% exhibiting low empathy, and 12% demonstrating high empathy. The internship duration, empathy satisfaction, secondary traumatic stress, only child, place of birth, and satisfaction with nursing were identified as factors influencing the latent profiles of empathy in nursing interns (p < 0.05). Conclusion There is considerable heterogeneity in nursing interns’ ability to empathize. Consequently, nursing educators and administrators should direct greater attention to interns with lower empathy and develop targeted intervention strategies based on the influences of the different underlying profiles.